Global burden of musculoskeletal disorders and attributable factors in 204 countries and territories: a secondary analysis of the Global Burden of Disease 2019 study - Binyan Wang; Ding Ye; Shiwen Liu; Shuzhen Fan; Yaxuan Wang; Yuxuan Zhan (BMJ Open)
Objective To evaluate the global burden of musculoskeletal (MSK) disorders, as well as the five common conditions, and their relevant risk factors from 1990 to 2019.Design Data from the Global Burden of Disease Study 2019 were used in this study.Setting and participants Individuals of all ages and genders from 204 countries and territories in 21 regions.Main outcome measures The outcomes were the numbers and age-standardised rates (ASRs) of incident cases, deaths and disability-adjusted life-years (DALYs) of MSK disorders. The average annual percent changes (AAPCs) in the ASRs were calculated using joinpoint regression analysis to estimate the trends.Results There were 322.75 million incident cases, 117.54 thousand deaths and 150.08 million DALYs of MSK disorders in 2019. The age-standardised incidence rate and age-standardised DALY rate in 2019 (incidence: AAPC=−0.32, 95% CI −0.34 to −0.31; DALYs: AAPC=−0.05, 95% CI −0.06 to −0.04) were lower than those in 1990. However, the age-standardised death rate showed a stable trend (AAPC 0.05, 95% CI −0.05 to 0.15) from 1990 to 2019. The peak age of onset and DALYs of MSK disorders was 50–54 years in 2019. The burden of MSK disorders in females was much higher than that in males (1.29 times more incident cases, 2.24 times more deaths and 1.45 times more DALYs in females than in males). A significant negative correlation was observed between the AAPCs in the ASRs and the Sociodemographic Index (SDI) score. Occupational risk exhibited the highest contribution to MSK disorders, and tobacco use and high body mass index were also major risk factors.Conclusions This study demonstrates that the burden of MSK disorders tends to be lower in high-SDI regions than in lower-SDI regions. Strengthening the effectiveness of preventive measures against occupational risks may reduce the burden of MSK disorders.